2012
DOI: 10.1089/apc.2012.0159
|View full text |Cite
|
Sign up to set email alerts
|

HIV Providers' Perceptions of and Attitudes Toward Female Versus Male Patients

Abstract: As a first step in understanding the role that health care

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…20 A small survey of 37 HIV providers reported more ''frustration'' with women patients compared with men and rated women as less educated, rational, responsible, compliant, independent, and direct compared with male patients. 21 The generalizability of these findings is unknown, but failure to recognize key information needs of women and having more frustrating interactions with women may reduce opportunities to provide relatedness support in the clinical setting. Low levels of relatedness support may help explain why women are less likely to effectively engage in HIV care than men, which would be consistent with Self-Determination Theory.…”
Section: Introductionmentioning
confidence: 99%
“…20 A small survey of 37 HIV providers reported more ''frustration'' with women patients compared with men and rated women as less educated, rational, responsible, compliant, independent, and direct compared with male patients. 21 The generalizability of these findings is unknown, but failure to recognize key information needs of women and having more frustrating interactions with women may reduce opportunities to provide relatedness support in the clinical setting. Low levels of relatedness support may help explain why women are less likely to effectively engage in HIV care than men, which would be consistent with Self-Determination Theory.…”
Section: Introductionmentioning
confidence: 99%
“…A potential confounding factor may be HIV care providers' negative perceptions of female versus male patients, resulting in gender disparities in HIV care. 18 This may potentially lead to lower adherence rates in women compared with men. Although the survey respondents overall represented the participants in the GRACE trial, there were some small differences.…”
mentioning
confidence: 99%
“…Adherence to HCV therapy is an important predictor of SVR (McHutchison et al, 2002). A study examining health disparities in HIV, demonstrated that women were less likely to be high school educated and employed compared with men (Blackstock et al, 2012). Less education and decreased financial support negatively impacted treatment success.…”
Section: Discussionmentioning
confidence: 99%